Biography, Legend and Heritage of Nomch mergen gegeen L.Luvsandambiidomei - Ganbold, Batmunkh; Damdinbaatar, Lkhagvagerel (Mongolian Language and Literature Studies, 2025)
The article clarifies some facts related to the biography of Nomch Mergen Gegeen L. Luvsandambiidome, the 6th reincarnation of Khorlo Chorji Lama from the Sartuul Setsen Zasag banner of Zasagt Khan aimag. It also addresses discrepancies in dates found in researchers' works and the publication status of his artistic works, offering the author's own proposals and conclusions. Furthermore, the author compares an oral legend about Nomch Mergen Gegeen, recorded from the elderly Dagva's Nyama, with two previously published versions. The article also notes that the reincarnation's personal possessions, specifically his mala, bowl, and dice, are currently preserved by the descendants of his disciple A. Natsuren. Номч мэргэн гэгээн Л.Лувсандамбийдомэйн намтар, домог, өв Хураангуй: Өгүүлэлд Засагт хан аймгийн Сартуул сэцэн засгийн хошууны Хорло цорж ламын VI дүр Номч мэргэн гэгээн Л.Лувсандамбийдомэйн намтарт холбогдох зарим мэдээ баримт, судлаачдын бүтээлд буй он цагийн зөрүү, уран бүтээлийг хэвлэн нийтэлсэн байдал зэргийг тодруулж өөрийн санал дүгнэлтийг дэвшүүлжээ. Мөн зохиогч өндөр настан Дагвын Нямаас тэмдэглэж авсан Номч мэргэн гэгээний аман домгийг урьд нь хэвлэгдсэн хоёр хувилбартай харьцуулж, хувилгааны эдэлж хэрэглэж байсан эрих, аяга, шоо нь түүний шавь А.Натсүрэнгийн удмынханд өдгөө хадгалагдаж буйг өгүүлжээ. Түлхүүр үгс: хувилгаан, домог, намтар, Лувсанравдандорж